Ádám Mészáros: 1978-2021 (Academic Journal of Internal Affairs, 2021)
Dr. Ádám Mészáros, who died of COVID-19 infection on April 6, 2021, Senior Research Fellow, Deputy Head of Department, Institute of Criminology, the Faculty of Law of the University of Pécs and Criminology and Lecturer in the Department of Penitentiary Law and in PTE Instructor of the Doctoral School.
Keywords: memoires